Auto zone - El-Khalil, Raed (2011)
Lean manufacturing processes provide tools and methods that focus on eliminating waste and adding value to assembly and manufacturing operations. Standardized work is the first tool in the continuous improvement process and one of the most powerful tools in lean manufacturing. Standardizing work initially focuses on documenting the current state of a job or workstation to establish a current best practice analysis. Three main pieces or information are essential for establishing a standardized work document: 1. customer demand rate (takt time), 2. operator work sequence, and 3. standard in-process stock (inventory). Zone 1 of the trim department is the first stage in the assembly department. The Zone 1 area includes eight stations. Implementing such improvements in all eight stations increased utilization but also increased idle time. The standardization process enabled the establishment of precise procedures for each auto zone technician.